CENOZOIC TECTONIC EVOLUTION OF THE EASTERN RHODOPE MASSIF (BULGARIA): BASEMENT STRUCTURE AND KINEMATICS OF SYN-TO POSTCOLLISIONAL EXTENSIONAL DEFORMATION - Bonev N. (My University, 2006)
This article contributes to a better understanding of the structure and extensional tectonics in the eastern part of the Rhodope massif. The eastern Rhodope high-grade metamorphic basement includes a lower and an upper unit of continental and mixed continental-oceanic affinity, respectively. Both high-grade basement units are tectonically overlain by a low-grade Mesozoic unit representing a Late Jurassic-Early Cretaceous subduction-accretion complex, and altogether the metamorphic units are covered by a sedimentary unit of Late Cretaceous to Miocene syn- to post-tectonic sequences. Low-angle extensional detachments and mylonitic zones separate the lower high-grade unit in the footwall from the hangingwall, consisting of the upper highgrade unit, a low-grade Mesozoic unit, greenschists, and a sedimentary unit lying in fault contact with the detachments. The high-grade basement structure consists of large-scale metamorphic domes, the Kesebir and the Byala reka domes, characterized by an overall dome-shaped regional foliation pattern and associated northwestsoutheast- to northeast-southwest-trending stretching lineation. The Kesebir dome internally consists of distinct submassifs-namely, the Kesebir (s.s.), the Makaza, and the Veykata domes-distinguished from one another on the basis of structural and kinematic patterns. Asymmetric ductile fabrics and metamorphic crystallization/deformation relationships indicate that the basement rocks experienced two distinct events of Alpine deformation: SSE-SSW-oriented contraction related to nappe stacking and top-tothe- SSW and/or -NNE extension. Top-to-the-SSE-SSW ductile fabric elements are coeval with the main metamorphism in amphibolite facies and are associated with synmetamorphic thrust imbrication of the high-grade basement units. This contractional event occurred before intrusion of the latest Late Cretaceous-Paleocene granitoids (70-53 Ma) and is also indicated by the radiometric ages of metamorphism. The southdirected kinematics of this contractional event continued in lower metamorphic grade and temperature conditions, with top-to-the-SSW ductile to brittle extension in the Byala reka dome and top-to-the-NNE ductile rather than brittle extension in the Kesebir dome. Extension developed partly coeval and concurrent with the earlier stacking event through the operation of ductile to semiductile shear zones under a lowangle brittle detachment that led to tectonic denudation and exhumation of the lower high-grade unit of the footwall in the cores of large-scale metamorphic domes. The extensional exhumation was accompanied by widespread cooling of the footwall rocks in both large-scale domes between 42 and 37 Ma, followed by late faulting at 36-35 Ma. The kinematic pattern in the high-grade basement units is interpreted to reflect spatially and vertically partitioned shear sense and kinematic direction defined by stretching lineations in a metamorphic pile. This pattern formed in response to transition from crustal thickening to late orogenic extension. The syn- to postcollisional extension described herein was broadly coeval with and followed closure of the Vardar Ocean. Extension has accommodated tectonic denudation during the late stage of the collisional evolution of the Alpine orogenic belt in the eastern Mediterranean region. The structural and kinematic results indicate that the eastern Rhodope region represents an Early-Middle Tertiary extensional domain in the northernmost part of the late Alpine Aegean extensional province. © 2006 Geological Society of America.
Keywords: BASEMENT TECTONICS; BULGARIA; EASTERN RHODOPE; EXTENSION; Cretaceous; Jurassic; Miocene; Eocene; Paleocene; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен